UKRAINE CRISIS AND THE EUROPEAN SECURITY ORDER:: A CAUSE-EFFECT ANALYSIS (Journal of European Studies (JES), 2018)
The debate over the 2014 Ukraine crisis revolves around two major arguments. The first blames the West for the crisis, seeing it as the consequence of the Western pursuit of NATO-EU expansion to the post-Soviet region. The second holds Russia responsible for the crisis in view of its coercive policies vis-à-vis the post-Soviet states to keep them in its own “sphere of influence” and, thus, denying them the sovereign right to join the Western organizations – NATO and EU. There are other explanations for the Ukraine crisis such as Ukraine’s domestic instability and ethnic divisions, Putin’s external adventurism for regime stability, and weak Western reaction to the Russian aggression. But these are generally considered less important or untenable. This paper does not focus on discordant explanations of the Ukraine crisis as reflected in the mainstream debate. Instead it delves into the post-Cold War European security order and identifies its structural flaws that, over the years, resulted in an increased Russia-West strategic dissonance, ultimately exploding into a crisis in Ukraine. In addition, it looks into the ramifications of the Ukraine crisis and consequent developments for the European security order. The principal question of this research is: What has lead Russia to perceive NATO-EU expansion to the post-Soviet region as a zero-sum-game and undertake coercive tactics to obstruct it? This study concludes that the post-Cold War European security order, founded on the centrality of the EU and NATO, was a great success in terms of post-Communist stabilization of Eastern and Central Europe. However, it failed to accommodate Russia as an equal partner. This structural problem put Russia and the West on a collision worse over Ukraine’s strategic alignment. However, the crisis has significantly strained the European security order, and would potentially be a turning point in this regard.
Keywords: Ukraine crisis; European security order,; geopolitics,; NATO; Russia; European Union